(untitled) (Web of Teachers: Inderscience Research, 2025)
In the process of geography education, the acquisition of cartographic knowledge by academic lyceum students is of particular importance. By its nature, this type of knowledge creates broad opportunities for students not only in their academic activities but also in everyday life, such as constructing buildings, ensuring access to water sources (wells), cultivating land, developing professional farming or household plots, organizing production and trade, selecting geographically favorable areas, and establishing cooperation with business partners. Therefore, when organizing geography education in academic lyceums, serious attention must be paid to ensuring the thorough mastery of cartographic knowledge by students. This article discusses the key aspects that should be considered in order to achieve a solid acquisition of cartographic knowledge among academic lyceum students.